The Protective Effect of Hydroalcoholic Extract of Roscoe (Ginger) on Ethanol-Induced Reproductive Toxicity in Male Rats - Abolfazl Akbari PhD; Khadijeh Nasiri PhD; Mojtaba Heydari MD, PhD; Seyed Hamdollah Mosavat MD, PhD; Aida Iraji PhD Candidate (SAGE Publishing, 2017)
This study was conducted to evaluate the prophylactic effect of ginger extract on ethanol-induced reproductive toxicity in male rats. Twenty-eight adult male Sprague-Dawley rats were randomly divided into 4 groups and treated daily for 28 days as follows: control, control-ginger (1 g/kg of body weight [BW]/day by gavage), ethanol group (ethanol 4 g/kg of BW/day by gavage), and ginger-ethanol group. At the end of the experiment, all the rats were sacrificed and their testes were removed and used for measurement of the total homocysteine (tHcy), trace elements, antioxidant enzymes activity, and malondialdehyde (MDA). The results in the ethanol group indicate that ethanol decreased antioxidant enzymes activity and increased MDA and tHcy compared with the control groups ( P < .05). In ginger-ethanol group, ginger improved antioxidant enzymes activity and reduced tHcy and MDA compared to ethanol group ( P < .05). It can be concluded that ginger protects the ethanol-induced testicular damage and improves the hormonal levels, trace elements, antioxidant enzymes activity, and decreases tHcy and MDA.